Method for the analysis of free carbenes present after NHC-organocatalyzed transformations - Das, Tamal Kanti; Biju, Akkattu T. (European Journal of Organic Chemistry, 2017)
In N-heterocyclic carbene (NHC) based organocatalysis, usually, the free carbene is generated in situ by treatment of the azolium salt with a base. Described herein is a method for the analysis of the NHC present in the reaction flask after the NHC-organocatalyzed reaction. For this, the reaction mixture was treated with elemental sulfur after the reaction and the thus-formed thiourea/thione derivative was isolated. Common NHC-catalyzed transformations such as benzoin reactions, Stetter reactions, homoenolate annulation reactions, and reactions proceeding via the ,-unsaturated acylazolium intermediate have been studied. The results indicate that after the reactions, 28-84% of the initial carbenes exist in the free form.